Assessment of the risk of falls among elderly persons in primary care settings - Suzana Savić; Larisa Gavran; Verica Petrović; Gordana Tešanović; Olivera Batić-Mujanović; Goran Borjanović (Medicinski glasnik, 2024)
Aim: To investigate the risk for falls in elderly patients treated in the Primary Health Care Centre Gradiška, Bosnia and Herzegovina. Methods: This study included 500 patients aged 65 and older. They were chosen randomly by 10 family physicians. Data collection took place every Wednesday and Friday, between January 2022 and July 2022. The patients' gait and balance assessments were performed using the Tinetti Gait and Balance Tool to assess the risk of falls. A supplementary questionnaire was created to record data about the patients' age, sex, chronic diseases, and drugs they take. Results: Among the included patients there were 266 females (53.2%) and 234 (46.8%) males, with the mean age of 75.25 years. The Tinetti test showed that the risk of falls was high for patients older than 75 years, 111 patients (69.8%), and 48 patients (30.2%) aged 65 to 74 (p=0.000). The risk of falling was higher for female, 93 (35%), than male patients, 66 (28.2%) (p=0.018). Considering chronic diseases, a high risk of falls was found in 32 (2.1%) patients with heart failure (p=0.029) and 19 (11.9%) patients with osteoporosis (p=0.000). Patients who used antihypertensive drugs had the highest risk for falls, 124 (78.0%) (p=0.757). Conclusion: About two-thirds of the examinees over the age of 75 had a high risk of falls, which indicates that family doctors should be more involved in fall prevention of elderly patients and consistently educate older patients and their families about it.
Keywords: elderly patients; fall prevention; family physicians